Interpretation of pipe-jacking and lubrication records for drives in silty soil - O'Dwyer, KG; McCabe, BA; Sheil, BB (Elsevier, 2019)
In recent years, there has been an increased resort to microtunnelling/pipe-jacking as a means of constructing underground conduits (for water, sewage, gas, and other utilities) to avoid on-street disruption in urban areas. In this paper, technical details of two 1 200 mm internal diameter microtunnels in silty sand totalling over 550 m in length are discussed. While average skin friction values are extremely low for both drives suggesting effective lubrication practice, differences in normalised bentonite volumes appear to be responsible for differences in skin friction. Full or near full buoyancy of the pipeline has been demonstrated for the majority of the drive. The frictional stress increase after a stoppage is shown to depend on not only the stoppage duration but also on the normalised lubrication volume. Interpretation of data in the manner presented in the paper is an important means of assimilating experience of microtunnelling in different ground conditions.